(untitled) (Web of Teachers: Inderscience Research, 2024)
This article looks at how Uzbekistan’s changing work culture shows how online work affects companies and workers’ satisfaction. A survey analysis shows the main trends in choosing to work from home or in a mixed work, as well as the performance outcomes that are expected. Study shows that problems with participations and effectiveness still exist, even though many employees may gain from having more open hours. There are two suggestions: make it easier for people to work from home and find a balance between the health and productivity of employees. This information could help companies develop in with and use better methods for letting people work from home in the future.